A facile approach to manufacturing non-ionic surfactant nanodipsersions using proniosome technology and high-pressure homogenization. (March 2015) - Najlah, Mohammad; Hidayat, Kanar; Omer, Huner K.; Mwesigwa, Enosh; Ahmed, Waqar; AlObaidy, Kais G.; Phoenix, David A.; Elhissi, Abdelbary
Abstract In this study, a niosome nanodispersion was manufactured using high-pressure homogenization following the hydration of proniosomes. Using beclometasone dipropionate (BDP) as a model drug, the characteristics of the homogenized niosomes were compared with vesicles prepared via the conventional approach of probe-sonication. Particle size, zeta potential, and the drug entrapment efficiency were similar for both size reduction mechanisms. However, high-pressure homogenization was much more efficient than sonication in terms of homogenization output rate, avoidance of sample contamination, offering a greater potential for a large-scale manufacturing of noisome nanodispersions. For example, high-pressure homogenization was capable of producing small size niosomes (209 nm) using a short single-step of size reduction (6 min) as compared with the time-consuming process of sonication (237 nm in >18 min) and the BDP entrapment efficiency was 29.65% ± 4.04 and 36.4% ± 2.8. In addition, for homogenization, the output rate of the high-pressure homogenization was 10 ml/min compared with 0.83 ml/min using the sonication protocol. In conclusion, a facile, applicable, and highly efficient approach for preparing niosome nanodispersions has been established using proniosome technology and high-pressure homogenization.